Utilization of fish oil for biodiesel production - Tri Nugroho Widianto; Bagus Sediadi Bandol Utomo (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2010)
Recenty fossil fuel consumption gradually increases, resulting in decreases of its naturalresource and causing environmental problems such as air pollution and global warming.Attempts to overcome the problems have been made to create on alternative energy such asbiodiesel from jatropha, microalgae and fish oil. Biodiesel production, as matter of fact, can beconducted using industrial wastes of fish meal, fish fillets and fish canning by transesterification offish oil using methanol and alkaline catalyst. Transesterification reaction kinetics must beconsidered for an efficient process. Transesterification rate constant very much depends on thetemperature and the quantity of the catalyst